Suitability of ANN applied as a hydrological model coupled with statistical downscaling model: a case study in the northern area of Peninsular Malaysia - Hassan Z.; Shamsudin S.; Harun S.; Malek M.A.; Hamidon N. (Springer Verlag, 2023)
Atmospheric temperature; Climate models; Neural networks; Rain; Rivers; Runoff; Water resources; General circulation model; Global surface temperature; Ihacres; Malaysia; Regional climate changes; River runoffs; Statistical downscaling; Statistical downscaling model (SDSM); Climate change; artificial neural network; climate change; hydrological modeling; river flow; runoff; simulation; statistical analysis; watershed; Malaysia; West Malaysia